2008
DOI: 10.1158/0008-5472.can-07-5301
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Tumor Immunosurveillance via Targeting of Interleukin-13 Receptor-α2

Abstract: In previous studies, we described a''counter-immunosurveillance'' mechanism initiated by tumor-activated, interleukin-13 (IL-13)-producing natural killer T cells that signal Gr-1 + cells to produce transforming growth factor-B 1 (TGF-B 1 ), a cytokine that suppresses the activity of tumor-inhibiting cytolytic CD8 + T cells. Here, we show that in two tumor models (the CT-26 metastatic colon cancer and the 15-12RM fibrosarcoma regressor models), this counter-surveillance mechanism requires the expression of a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 26 publications
5
76
0
Order By: Relevance
“…It was assumed that lung metastasis was not significantly enhanced following etanercept treatment in the present study, as etanercept exhibited little effect on NK cells. This finding does not conflict with previous studies reporting that TNF blockade inhibits carcinogenesis and cancer metastasis (41,42).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…It was assumed that lung metastasis was not significantly enhanced following etanercept treatment in the present study, as etanercept exhibited little effect on NK cells. This finding does not conflict with previous studies reporting that TNF blockade inhibits carcinogenesis and cancer metastasis (41,42).…”
Section: Discussionsupporting
confidence: 69%
“…Etanercept has been reported to reduce the number and size of tumors in a spontaneous colon cancer mouse model associated with chronic colitis (40). Furthermore, blockade of TNF-α has been reported to inhibit lung metastasis in a mouse model (41,42). Concerning the effect of etanercept on NK cells, etanercept was reported to inhibit the production of transforming growth factor (TGF)-β1, which subsequently led to the inhibition of NK cells and cytotoxic activity (42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, a previous study demonstrated that CD11b + Gr-1 + cells isolated from mice with EAE inhibited T cell proliferation in co-culture with naive CD4 cells, but promoted Th17 cell differentiation under Th17-polarizing conditions (71). Another study demonstrated that activation of the suppressive function of M-MDSCs occurred at the peak of EAE disease (72). This aforementioned study determined that the suppression of T cell responses was due to M-MDSC-mediated NO production (72).…”
Section: Mdscs and Experimental Autoimmune Encephalomyelitis (Eae)mentioning
confidence: 99%